The Role of Imam Ali ibn e- Mohammad (PBUH) in regard with the Cultural Management of Islamic Nation - Asqar Montazer al- Qaem; bahman zeinali (تاریخ اسلام, 2018)
Imam Ali ibn e- Mohammad (PBUH) was the intellectual and cultural leader of Shiites in chaotic age full of political riot and sedition from 220 to 254 After Hijrah. That holiness was of divine Imamate status, supreme training, insight, intelligence, cultural and immense science as well as grand cultural behavior. In this regard, Imam Hadi (PBUH) was of strong strategy and cultural motivation towards the cultural management so that he could take strategies intended for the cultural leading of community as well as the cultural organization, scientific and educative development, Putting emphasis on the development of science and instruction, propagation of science and thought, development of the center for the confidential relationships among agents, training personnel, development of the charter of lifestyle and legislation, illustration of citizen’s right, clarifying coexistence regulations of Muslims and people of The Book and the cultural fight against ignorant behavior of Abbasid caliphs such as Motevakel, and he  succeeded to make cultural changes among the Islamic nation and to provide the ground for achieving the health and happiness of Islamic community.  Utilizing the descriptive-analytical method, the present article studies the cultural management of Islamic nation by Imam Hadi (PBUH) and tests this hypothesis that Imam Hadi as a divine leader provided the ground for the cultural management by recognition of the intellectual and cultural trends of his time with the centrality of the guidance of community by taking various strategies and succeeded to make intelligent changes and guide the community.